Biocompatibility and biomineralization assessment of bioceramic-, epoxy-, and calcium hydroxide-based sealers - Bueno, Carlos Roberto Emerenciano; Valentim, Diego; Marques, Vanessa Abreu Sanches; Gomes-filho, João Eduardo; Cintra, Luciano Tavares Angelo; Jacinto, Rogério Castilho; Dezan-junior, Eloi (Sociedade Brasileira de Pesquisa Odontológica - SBPqO, 2016)
Obturation of the root canal system aims to fill empty spaces, promoting hermetic sealing and preventing bacterial activity in periapical tissues. This should provide optimal conditions for repair, stimulating the process of biomineralization. An endodontic sealer should be biocompatible once it is in direct contact with periapical tissues. The aim of this study was to evaluate the rat subcutaneous tissue response to implanted polyethylene tubes filled with Smartpaste Bio, Acroseal, and Sealapex and investigate mineralization ability of these endodontic sealers. Forty Wistar rats were assigned to the three sealers groups and control group, (n = 10 animals/group) and received subcutaneous implants containing the test sealers, and the control group were implanted with empty tubes. After days 7, 15, 30, and 60, animals were euthanized and polyethylene tubes were removed with the surrounding tissues. Inflammatory infiltrate and thickness of the fibrous capsule were histologically evaluated. Mineralization was analyzed by Von Kossa staining and polarized light. Data were tabulated and analyzed via Kruskal-Wallis and Dunn’s test. All tested materials induced a moderate inflammatory reaction in the initial periods. Smartpaste Bio induced the mildest inflammatory reactions after day 15. No difference was observed among groups after days 30 or 60. Von Kossa-positive staining and birefringent structures observed under polarized light revealed a larger mineralization area in Sealapex-treated animals followed by Smartpaste Bio-treated animals. At the end of the experiment, all tested sealers were found to be biocompatible. All sealers induced biomineralization, except Acroseal, which induced a mild tissue reaction.
Keywords: Inflammation; Calcium Hydroxide; Endodontics